How Scholars Think about Greenwashing Over the Last Two Decades. An Overview through a Bibliometric Analysis - NAGY-KERCSÓ, Katalin; KONTOR, Enikő (Journal of Environmental Management and Tourism; Vol 15 No 2 (2024): JEMT, Volume XV, Issue 2(74), Summer 2024DO - 10.14505/jemt.v15.2(74).04, 2024)
Bibliometric analysis is a widely recognized approach for examining extensive scientific data sets. However, its application is relatively new, particularly in greenwashing within the environment. As a comprehensive concept, sustainability encompasses various aspects, and greenwashing has emerged as a specific branch that has garnered increased attention and research in recent years. The study's primary purpose is to deploy the bibliometric method to analyze greenwashing literature from 2003 to 2023 using the Web of Science Core Collection and VOSviewer software to identify and visualize the intellectual landscape of the field. The number of scientific publications related to the topic confirms the importance and popularity of the subject. In this period, a total of 807 publications on the topic of greenwashing were identified, and three different periods were set. Most publications and citations primarily come from the USA, China, and other developed European countries. In terms of journals, prominent publications hold positions in the top 10, such as the Journal of Business Ethics, Journal of Cleaner Production, Business Strategy and The Environment, and Sustainability. The topic mainly concerns social and natural sciences branches, emphasizing corporate social responsibility and environmental concerns. Regarding keywords, four clusters can be distinguished as being in the center of governmental, consumer, corporate, and management issues. The ongoing trends predict a persistent rise in worldwide publications regarding greenwashing.